New Oscillation Results of Second-Order Damped Dynamic Equations with p-Laplacian on Time Scales - Yang-Cong Qiu; Qi-Ru Wang (Discrete Dynamics in Nature and Society, 2015)
By employing a generalized Riccati technique and functions in some function classes for integral averaging, we derive new oscillation criteria of second-order damped dynamic equation with p-Laplacian on time scales of the form (rtφγ(xΔ(t)))Δ+ptφγ(xΔ(t))+f(t,x(g(t)))=0, where the coefficient function p(t) may change sign. Two examples are given to demonstrate the obtained results.